2018
DOI: 10.3389/fnagi.2018.00092
|View full text |Cite
|
Sign up to set email alerts
|

Influence of APOE and RNF219 on Behavioral and Cognitive Features of Female Patients Affected by Mild Cognitive Impairment or Alzheimer’s Disease

Abstract: The risk for Alzheimer’s disease (AD) is associated with the presence of the 𝜀4 allele of Apolipoprotein E (APOE) gene and, recently, with a novel genetic variant of the RNF219 gene. This study aimed at evaluating interactions between APOE-𝜀4 and RNF219/G variants in the modulation of behavioral and cognitive features of two cohorts of patients suffering from mild cognitive impairment (MCI) or AD. We enrolled a total of 173 female MCI or AD patients (83 MCI; 90 AD). Subjects were screened with a comprehensiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 61 publications
0
6
0
Order By: Relevance
“…A recent study shows that RNF219 is able to promote DNA replication origin firing through ubiquitination of the ORC complex (22). A genetic variant of the RNF219 gene was reported to be associated with the risk for Alzheimer's disease (23). Here we biochemically identified RNF219 as an interacting factor of CCR4-NOT.…”
Section: Introductionmentioning
confidence: 72%
“…A recent study shows that RNF219 is able to promote DNA replication origin firing through ubiquitination of the ORC complex (22). A genetic variant of the RNF219 gene was reported to be associated with the risk for Alzheimer's disease (23). Here we biochemically identified RNF219 as an interacting factor of CCR4-NOT.…”
Section: Introductionmentioning
confidence: 72%
“…Evidence of upregulation of Rnf182 in the brain of AD patients suggests that Rnf182 is involved in the pathophysiological process of AD via induced degradation of ATP6V0C, a key component of the gap junction and neurotransmitter release pathway in the brain. 61 Genetic variations in Rnf219 increase the risk of AD, 62 while Rnf40 has been associated with learning and memory behavior in rats. 63 Our analysis demonstrated that Rnf20 may affect the expression of both pain sensitivity and cognitive function through the PI3K-Akt signaling pathway.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, among non-demented individuals, APOE e4 carriers display more pronounced atrophy in the amygdala compared to APOE e3/e3 individuals [ 36 ], although there is also evidence not confirming these results [ 33 ]. Interestingly, the APOE e4 allele may also interact with RNF219/G variants to affect anxiety levels in women with MCI [ 37 ]. Ring finger (RNF) proteins have been implicated in myelin production, synaptic stability, and ubiquitin system regulation [ 37 ].…”
Section: The Relationship Between Apolipoprotein E (Apoe) Genotype An...mentioning
confidence: 99%